Exploring two dimensional Co0.33In2.67S2.29Se1.71 as alloy type negative electrode for Li-ion battery with olivine LiFePO4 cathode - Chaturvedi, Apoorva (2020)
We report the synthesis and Li-storage properties of two-dimensional Co0.33In2.67S2.29Se1.71 as an anode for Li-ion battery applications. Chemical vapour transport technique is adopted to prepare high quality Co0.33In2.67S2.29Se1.71 single crystals with high yield. Li-storage properties are assessed using a half-cell configuration in which the cell is cycled in the alloying region (0.005–1 V vs. Li) that provides better characteristics than the extended region (i.e. allowing the materials to undergo a conversion pathway) in terms of cycling stability and retention. This logically think us to evaluate the suitability of the prepared negative electrode to fabricate the practical cell i.e. full-cell with olivine phase LiFePO4 cathode. The irreversible capacity loss observed in the negative electrode is effectively tackled by using an electrochemical pre-treatment with Li and subsequently assembled the full-cell by adjusting the loading of LiFePO4. The practical-cell, LiFePO4/pre-treated Co0.33In2.67S2.29Se1.71 displayed a very decent electrochemical activity and exhibits a maximum energy density of ∼103 Wh kg−1 (including dead mass weight).